THE EFFECT OF PROFITABILITY AND LEVERAGE ON AGGRESSIVENESS OF TAXES ON MINING SECTOR CORPORATES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD - Fadjar, Achmad; Muslim, Muhammad Yogi; Rindiansyah (CENTRAL ASIA AND THE CAUCASUS, 2022)
Aggressiveness of tax is an action taken by taxpayers whose purpose is actually simple, namely wanting to minimize the tax burden received either through corporate policy or maximize the efficiency of the tax received by maximizing the weakness of generally accepted tax rules in Indonesia. This study aims to determine the factors that affect aggressiveness of tax, namely profitability and leverage. The object of this research is Profitability, Leverage and Aggressiveness of tax in mining sector Corporates listed on the Indonesia stock exchange. Thepurposive sampling result in this study were 31 Corporates during the 2018-2020 period. The analytical technique used in this study is multiple regression analysis with data processing tools, namely SPSS. The results showed that Profitability and Leverage had an effect on Aggressiveness of Tax.